Analisis Pengaruh Literasi, Motivasi, Persepsi, dan Pendapatan Terhadap Minat Mahasiswa Menggunakan Produk Reksadana Syariah (Study Kasus Mahasiswa FEBI UINSU ) - Bambang Suriadi (ITB AAS INDONESIA Surakarta, 2022)
One of the investments currently being developed is Mutual Funds. Mutual funds are a place to coll ect funds from the public which will then be placed in a portfolio. Basic investment knowledge is very important for potential investors to know. This research was conducted using a quantitative method with a sample of 76 respondents taken from students of the State Islamic University of North Sumatra. The data analysis technique was carried out through validity, reliability, normality test, multiple regression analysis test, coefficient of determination test and hypothesis testing F and t. The results of the quantitative analysis are that literacy has an effect on public interest with a t-count value of X1 = 22,159 and a significance of 0.033 5%. Income has an effect on public interest with a tcount value of X4 = 2.064 and a significance of 0.011 < 5%. Literacy, Motivation, Perception and Income have a positive effect on Public Interest with R. Square 43.3% and F test = 18.114 and significance value = 0.000